Empiric Recurrence Risk Estimates for Chronic Tic Disorders: Implications for Genetic Counseling - Heiman, Gary A.; Rispoli, Jessica; Seymour, Christine; Leckman, James F.; King, Robert A.; Fernandez, Thomas V. (Frontiers in Neurology, 2020)
Background: Tourette disorder (TD) and other chronic tic disorders are neurodevelopmental/neuropsychiatric disorders characterized by motor and/or vocal tics. Family studies indicate that TD strongly aggregates within families and that other chronic tic disorders are biologically related such that studies typically combine them into any chronic tic disorder (CTD). Because of stigma, bullying, and comorbidity with other neuropsychiatric disorders, CTDs can severely impact the quality of life of individuals with these disorders. Objectives: The genetic architecture of CTDs is complex and heterogeneous, involving a myriad of genetic variants. Thus, providing familial recurrence risks is based on empirical recurrence risk estimates rather than genetic testing. Because empiric recurrence risks for CTDs have not been published, the purpose of this study is to calculate and report these recurrence risks estimates. Methods: Based on population prevalence and increased risk to different relatives from a large population-based family study, we calculated the empiric recurrent risk estimate for each relative type (full sibling, parents, offspring, all first-degree, and all second-degree). Results: The recurrence risk estimate for CTDs in first-degree relatives is 29.9% [95% confidence interval (CI) = 23.2–38.5%]. The risk is higher in males, 33.7% (95% CI = 26.2–43.3%), than females, 24.3% (95% CI = 18.9–31.3%). Conclusions: Given the complex, heterogeneous genetic architecture of CTDs, individuals concerned about recurrence risk should be referred to genetic counseling. Such counseling should include discussion of the derivation and limitations of these empiric recurrence risk estimates, including the upper and lower limits of the range of risk.